1963
DOI: 10.1177/004051756303300601
|View full text |Cite
|
Sign up to set email alerts
|

Nonwoven Fabric Studies

Abstract: he variatiot; of tensile stre~gth with test specimen length (jaw span) has been ex-amIned theoretically and exper.lmentally for a range of nonwoven fabrics. It is shown that the plot o~stre.n.gth ,:ersus Jaw span provides a basis for assessing the extent to which fiber~trengt~IS utlh~ed. In a bo~ded fiber system, weakness due to poor bonding being associated wlth.a rapid Increase In s:rength as the jaw span is decreased below the fiber length. By this method, the relative bonding strengths of several commercia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1965
1965
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Grouping of the measurements of curl factor and orientation on the fiber segments is unnecessary; each one is used individually. The results from six fahrics are demon- In a previous experiment described by Michie [5], the zero jaw-span test had been carried out on several nonwovens.…”
Section: Comparison Of Theory and Experimentsmentioning
confidence: 99%
“…Grouping of the measurements of curl factor and orientation on the fiber segments is unnecessary; each one is used individually. The results from six fahrics are demon- In a previous experiment described by Michie [5], the zero jaw-span test had been carried out on several nonwovens.…”
Section: Comparison Of Theory and Experimentsmentioning
confidence: 99%
“…Both the influence of single fiber strength and fiber orientation as well as the influence of pressure and temperature in the calendering process have been investigated and modeled in detail in numerous studies. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] It has been shown that the pressure has only a limited influence, [7,[15][16][17][18] whereas the temperature has a significant influence on the strength of nonwovens, whereby for polypropylene, a maximum strength is achieved at temperatures between 140 and 155 C depending on the weight per area, fiber diameter, process speed, and polymer grades used. [7,8,12,19,20] Generally, it is important that a temperature of at least 132 C is reached in the core of the nonwoven, whereas too high average temperatures in the web of over 142 C can lead to delamination of the bonding points or to an increased weakening at the edge of the bonding points.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical properties depend both on the properties of the filaments and on the bonding of the fibers. Both the influence of single fiber strength and fiber orientation as well as the influence of pressure and temperature in the calendering process have been investigated and modeled in detail in numerous studies . It has been shown that the pressure has only a limited influence, whereas the temperature has a significant influence on the strength of nonwovens, whereby for polypropylene, a maximum strength is achieved at temperatures between 140 and 155 °C depending on the weight per area, fiber diameter, process speed, and polymer grades used .…”
Section: Introductionmentioning
confidence: 99%